Preparation method of wear-resistant high-strength lake green high-borosilicate glass
Patent Information
- Application Number
- CN202611320062.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-27
AI Technical Summary
但是该专利技术缺少对玻璃耐磨性能的研究,同时弯曲强度也有提升的空间
(1)本发明的复合改性二氧化硅中稀土离子通过高场强积聚作用和网络稳定化效应,从微观上强化了玻璃基体的骨架,而致密的硼铝硅酸盐包覆层则通过化学键合修复了表面缺陷,并提供了高硬度的耐磨保护层;两者协同作用,最终实现了高硼硅玻璃耐磨性和弯曲强度的全面提升。
Smart Images

Figure CN122977700A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of special glass technology, specifically relating to a method for preparing wear-resistant, high-strength, lake-green high borosilicate glass. Background Technology
[0002] High borosilicate glass is a special type of glass with unique properties. Compared to ordinary glass, it contains a high proportion of boron and silicon, making it far superior in terms of heat resistance and chemical stability. It can easily withstand many extreme conditions that ordinary glass cannot withstand. High borosilicate glass has the following characteristics: (1) Excellent heat resistance. Its coefficient of thermal expansion is extremely low, about one-third that of ordinary glass. This means that it will hardly break due to uneven expansion when the temperature changes drastically; (2) Stronger chemical stability. It has strong resistance to the corrosion of water, acid, and alkali, and its chemical properties are very stable; (3) High light transmittance and low refractive index. It has excellent optical performance, high light transmittance, and is more crystal clear visually.
[0003] The general production process of high borosilicate glass is as follows: First, the loading loader loads the materials into the raw material bins, and the control host automatically proportions them. The materials are then automatically conveyed to the mixer by the screw feeder for automatic stirring. The uniformly stirred raw materials are automatically lifted to the kiln head bin by the bucket elevator, and then fed into the kiln by the fully automatic feeder. The dust generated during this process is removed by the spray tower dust removal system, and the exhaust gas emissions meet the requirements of the "Emission Standard of Air Pollutants for Industrial Furnaces and Kilns" (DB13 / 1640-2012). The kiln melts the materials into qualified glass liquid at high temperature by electric heating. The glass liquid flows through the flow channel and the riser, and then through the material channel for clarification and shaping to produce qualified glass products. Glass forming is divided into two types: the Verlo flat drawing method and the Verlo vertical drawing method. The Verlo flat drawing method uses an automatic flat drawing machine to cut the glass profiles of the required specifications, while the Verlo vertical drawing method uses an intelligent robot to precisely cut the formed glass profiles.
[0004] High borosilicate glass is used in many fields due to its excellent properties, including: (1) laboratory glassware, because it is resistant to chemical corrosion and heats evenly, it can be used in beakers, test tubes, graduated cylinders, distillation apparatus, etc., and is a standard configuration for chemical and biological laboratories; (2) kitchen and catering, including heat-resistant glass food storage boxes, oven-specific baking trays, microwave-specific bowls, double-walled glass cups, baby bottles and high-end teapots, etc.; (3) optics and lighting, solar collector tubes, astronomical telescope lenses, high-strength halogen lamp shades, stage lighting lenses, etc.; (4) industry and medicine, pharmaceutical glass bottles (especially pre-filled syringes), chemical pipeline sight glasses, fireproof observation windows, etc.
[0005] Chinese patent (publication number CN119330589B) discloses a method for preparing high-transparency borosilicate glass. This invention uses an aerogel method to prepare rare-earth chloride-treated silica as a silicon source for one part of the glass. Combined with the addition of phosphorus-modified lithium oxide flux, the final product is high borosilicate glass, which improves the glass's hardness and fracture toughness, reduces its coefficient of thermal expansion, and can prevent a decline in the glass's optical properties. However, this patented technology lacks research on the glass's wear resistance, and there is room for improvement in its flexural strength.
[0006] Therefore, there is an urgent need for a wear-resistant, high-strength lake-green borosilicate glass. Through component design and the introduction of functional materials, the borosilicate glass can be guaranteed to have good mechanical properties while effectively improving the wear resistance of the material. Summary of the Invention
[0007] To address the shortcomings of existing technologies, the present invention aims to provide a method for preparing wear-resistant, high-strength, lake-green high-borosilicate glass. The invention first uses rare earth elements to dope nano-silica to obtain rare earth-doped silica, then modifies the rare earth-doped silica to obtain composite-modified silica. Next, quartz sand, composite-modified silica, borax, boric acid, alumina, calcium oxide, inorganic salt additives, and chromium trioxide are mixed to obtain a mixture. This mixture is then melted at high temperature to obtain a glass melt, which is subsequently clarified, homogenized, pressed, and annealed to obtain wear-resistant, high-strength lake-green high-borosilicate glass. By introducing functional materials such as composite-modified silica, the present invention enables high-borosilicate glass to possess excellent wear resistance and flexural strength, making it better suited for applications in the field of specialty glass.
[0008] The technical solution adopted by the present invention to solve the above-mentioned technical problems is as follows: In a first aspect, this invention provides a method for preparing wear-resistant, high-strength, lake-green borosilicate glass, comprising the following steps: S1. First, rare earth elements are used to dope nano-silica to obtain rare earth-doped silica, and then the rare earth-doped silica is modified to obtain composite modified silica. S2. Quartz sand, composite modified silica, borax, boric acid, alumina, calcium oxide, inorganic salt additives, and chromium trioxide are mixed to obtain a mixture. The mixture is then melted at high temperature to obtain molten glass. S3. The glass melt described in step S2 is clarified, homogenized, pressed, and annealed to obtain wear-resistant, high-strength lake green borosilicate glass.
[0009] As a preferred technical solution of the present invention, the components in step S2 include, by weight: 80-90 parts of quartz sand, 10-20 parts of composite modified silica, 5-10 parts of borax, 5-10 parts of boric acid, 4-6 parts of alumina, 1-2 parts of calcium oxide, 1-2 parts of inorganic salt additives, and 0.4-0.6 parts of chromium trioxide.
[0010] As a preferred technical solution of the present invention, the weight parts of the quartz sand can be 80 parts, 82 parts, 84 parts, 86 parts, 88 parts or 90 parts, etc.
[0011] As a preferred embodiment of the present invention, the weight parts of the composite modified silica can be 10 parts, 12 parts, 14 parts, 16 parts, 18 parts, or 20 parts, etc.
[0012] As a preferred embodiment of the present invention, the weight parts of the borax can be 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts, etc.
[0013] As a preferred embodiment of the present invention, the boric acid may be expressed in parts by weight of 5, 6, 7, 8, 9, or 10, etc.
[0014] As a preferred embodiment of the present invention, the alumina may be in the following weight proportions: 4 parts, 5 parts, or 6 parts, etc.
[0015] As a preferred embodiment of the present invention, the weight parts of the calcium oxide may be 1.0 parts, 1.2 parts, 1.4 parts, 1.6 parts, 1.8 parts, or 2.0 parts, etc.
[0016] As a preferred embodiment of the present invention, the inorganic salt additive may be present in parts by weight of 1.0, 1.2, 1.4, 1.6, 1.8, or 2.0 parts, etc.
[0017] As a preferred embodiment of the present invention, the weight percentage of chromium trioxide may be 0.4 parts, 0.5 parts, or 0.6 parts, etc.
[0018] As a preferred technical solution of the present invention, the preparation steps of the rare earth-doped silica are as follows: by weight, 20-30 parts of lanthanum nitrate and 30-40 parts of yttrium nitrate are added to 180-200 parts of deionized water and stirred to dissolve to obtain a rare earth precursor solution. Then, 40-50 parts of nano silica are added for ultrasonic impregnation, filtered, and rare earth-impregnated silica is obtained. The rare earth-impregnated silica is then calcined at high temperature to obtain rare earth-doped silica.
[0019] As a preferred technical solution of the present invention, the high-temperature calcination step is as follows: the rare earth impregnated silica is transferred to a tube furnace, heated to 400~500℃ and held for 60~80 minutes, then heated to 1200~1300℃ and calcined for 4~6 hours, cooled to room temperature, washed with deionized water, and vacuum dried.
[0020] As a preferred embodiment of the present invention, the conditions for ultrasonic impregnation are: ultrasonic power of 200~400W, ultrasonic frequency of 20~30kHz, impregnation temperature of 50~60℃, and impregnation time of 4~6h.
[0021] In this invention, lanthanum nitrate and yttrium nitrate, as soluble rare earth nitrates, dissociate into rare earth cations in deionized water. These cations are then loaded onto the surface and pore walls of nano-silica through electrostatic adsorption and hydroxyl coordination adsorption. Subsequently, interfacial solid-phase diffusion is achieved through segmented high-temperature calcination, dispersing the rare earth components in the silica matrix to obtain rare earth modified silica.
[0022] As a preferred embodiment of the present invention, the modification treatment steps are as follows: Dissolve 20-30 parts by weight of aluminum isopropoxide in 30-50 parts by weight of isopropanol, then add 10-20 parts by weight of tetraethyl orthosilicate, and mix thoroughly to obtain an aluminum isopropoxide-tetraethyl orthosilicate mixed alcohol solution; add 6-8 parts by weight of boric acid to 90-100 parts by weight of deionized water, heat to 50-60°C and stir until the boric acid is completely dissolved, then keep warm to obtain a hot boric acid aqueous solution; under stirring conditions at 50-60°C, the hot... Aqueous boric acid was slowly added dropwise to a mixed alcoholic solution of aluminum isopropoxide and tetraethyl orthosilicate. The pH of the system was adjusted to 4.0-4.8 during the addition process. After the addition was completed, the solution was kept at a constant temperature for 2-4 hours to hydrolyze and obtain an aluminum-boron-silicon composite sol. 40-50 parts of rare earth-doped silica were added to the composite sol and ultrasonically dispersed for 1-2 hours. After drying at 100-110℃ for 4-6 hours, the solution was transferred to a tube furnace, heated to 700-800℃ and held at that temperature for 2-3 hours. The solution was then cooled with the furnace to obtain composite modified silica.
[0023] This invention uses aluminum isopropoxide, boric acid, and tetraethyl orthosilicate as raw materials to form a multi-element inorganic composite sol through hydrolysis-condensation. Then, rare earth-doped silica is added to the composite sol and ultrasonically enhanced wetting is performed. The sol colloidal particles are uniformly adsorbed and coated on the outer surface of the silica particles. Finally, a composite modified silica with a dense borosilicate layer is obtained by high-temperature treatment.
[0024] As a preferred technical solution of the present invention, the alumina is an alumina composite material; the preparation method of the alumina composite material is as follows: first, nano-alumina, nano-carbon powder, and nano-silicon powder are added to a tetraethyl orthosilicate solution to prepare an alumina coating, and then the alumina coating is subjected to high temperature and high pressure treatment to obtain the alumina composite material.
[0025] As a preferred embodiment of the present invention, the preparation steps of the alumina coating are as follows: by weight, 400-450 parts of anhydrous ethanol and 50-100 parts of deionized water are mixed, 40-50 parts of tetraethyl orthosilicate are added, the pH is adjusted to 4-5 and stirred at room temperature for 10-20 minutes to obtain a precursor solution; under a nitrogen inert protective atmosphere, 20-30 parts of nano-alumina are dispersed in 90-100 parts of anhydrous ethanol to obtain an alumina dispersion, 2-4 parts of nano-carbon powder are dispersed in 10-20 parts of anhydrous ethanol to obtain a carbon powder dispersion, and 0.8-1.2 parts of nano-silicon powder are dispersed in 8-10 parts of anhydrous ethanol to obtain a silicon powder dispersion; the alumina dispersion, carbon powder dispersion, and silicon powder dispersion are mixed and ultrasonically dispersed to obtain a powder-mixed ethanol dispersion, then the precursor solution is added and the mixture is heated to 65-70°C and stirred for 4-6 hours to coat the alumina, and then vacuum dried to obtain the alumina coating.
[0026] As a preferred technical solution of the present invention, the high temperature and high pressure treatment step is as follows: the alumina coating is placed in a high pressure sintering equipment, a pressure of 4~5GPa is applied first, then the temperature is raised to 1500~1600℃ under a nitrogen atmosphere and held for 15~25min, cooled to room temperature, and pulverized to obtain the alumina composite material.
[0027] This invention first uses tetraethyl orthosilicate as a precursor and employs a sol-gel method to prepare gelled coated alumina composite particles containing nano-carbon powder and nano-silicon powder in the surface coating. Subsequently, during high-temperature and high-pressure treatment, the silica in the gel reacts with the nano-alumina to form a mullite phase, while the nano-carbon powder and nano-silicon powder can form a silicon carbide phase on the alumina surface, ultimately obtaining an alumina composite material.
[0028] As a preferred embodiment of the present invention, the inorganic salt additive is selected from one or more of sodium chloride, potassium chloride, calcium sulfate, and zinc sulfate.
[0029] As a preferred technical solution of the present invention, the high-temperature melting step in step S2 is as follows: the mixture is transferred to a glass furnace, heated to 850~900℃ and held for 100~120 min, then heated to 1250~1300℃ and held for 30~40 min, and then heated to 1600~1650℃ and held for 120~140 min.
[0030] As a preferred technical solution of the present invention, the conditions for clarification and homogenization in step S3 are: the temperature for clarification and homogenization is 1500~1550℃, and the time is 20~30min.
[0031] As a preferred technical solution of the present invention, the pressing conditions in step S3 are: the pressing temperature is 1000~1050℃ and the pressing pressure is 15~20MPa.
[0032] As a preferred technical solution of the present invention, the annealing conditions in step S3 are as follows: first, the temperature is lowered to 500-550°C at a rate of 2-4°C / min, and then lowered to room temperature at a rate of 6-8°C / min.
[0033] Compared with the prior art, the beneficial effects of the present invention are: (1) In the composite modified silica of the present invention, rare earth ions strengthen the skeleton of the glass matrix from the microscopic level through high field strength accumulation and network stabilization effect, while the dense borosilicate coating repairs surface defects through chemical bonding and provides a high-hardness wear-resistant protective layer; the two work together to achieve a comprehensive improvement in the wear resistance and bending strength of high borosilicate glass.
[0034] (2) When the alumina composite material of the present invention is introduced into the borosilicate glass system, the mullite phase in the composite material improves the interfacial compatibility between the ceramic phase and the borosilicate glass matrix to achieve effective stress transfer. Under the action of external force, the hard particles can induce crack deflection and crack bridging, consume fracture energy, inhibit crack propagation, and improve the bending strength of the glass. Under friction and wear conditions, the high-hardness mullite and silicon carbide particles bear the friction load, reduce matrix peeling, and improve the wear resistance of the borosilicate glass. Attached Figure Description
[0035] Figure 1 The images show the XRD patterns of the alumina composite material and nano-alumina in Example 1 of this invention.
[0036] Figure 2 This is a transmission electron microscope image of the alumina composite material in Example 1 of the present invention. Detailed Implementation
[0037] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.
[0038] The sources of some components in the examples and comparative examples are as follows: Quartz sand, brand name SINO-FS, purchased from Jiangsu Zhongteng Quartz Materials Technology Co., Ltd. Nano silica, item number S104596, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Lanthanum nitrate, CAS No. 100587-94-8, was purchased from Sinopharm Chemical Reagent Co., Ltd. Yttrium nitrate, CAS No. 13494-98-9, was purchased from Sinopharm Chemical Reagent Co., Ltd. Aluminum isopropoxide, CAS No. 555-31-7, purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Borax, item number S736754, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Boric acid, CAS No. 10043-35-3, was purchased from Sinopharm Chemical Reagent Co., Ltd. Nano-alumina, item number A396574, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Nano carbon powder, item number C109965, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Nano-silicon powder, item number S130843, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. Tetraethyl orthosilicate, CAS No. 78-10-4, purchased from Sinopharm Chemical Reagent Co., Ltd. Calcium oxide, CAS No. 1305-78-8, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Sodium chloride, CAS No. 7647-14-5, was purchased from Sinopharm Chemical Reagent Co., Ltd. Potassium chloride, CAS No. 7447-40-7, was purchased from Sinopharm Chemical Reagent Co., Ltd. Calcium sulfate, CAS No. 10034-76-1, purchased from Sinopharm Chemical Reagent Co., Ltd. Chromium trioxide, CAS No. 1308-38-9, was purchased from Shanghai Maclean Biochemical Technology Co., Ltd. Example 1
[0039] This embodiment provides a method for preparing wear-resistant, high-strength, lake-green borosilicate glass, including the following steps: S1. By weight, 30 parts of lanthanum nitrate and 40 parts of yttrium nitrate were added to 200 parts of deionized water and stirred to dissolve, thus obtaining a rare earth precursor solution. Then, 50 parts of nano-silica were added for ultrasonic impregnation (ultrasonic power of 400W, ultrasonic frequency of 30kHz, impregnation temperature of 60℃, and impregnation time of 4h). After filtration, rare earth-impregnated silica was obtained. The rare earth-impregnated silica was transferred to a tube furnace, heated to 500℃ and held for 60min, then heated to 1300℃ and calcined for 4h. After cooling to room temperature, it was washed with deionized water and vacuum dried to obtain rare earth-doped silica. 30 parts of aluminum isopropoxide were dissolved in 50 parts of isopropanol, and then 20 parts of orthosilicic acid were added. Ethyl isopropoxide-tetraethyl isopropoxide mixed alcohol solution by thorough stirring; 6-8 parts of boric acid are added to 100 parts of deionized water, heated to 60℃ and stirred until the boric acid is completely dissolved, and kept at the temperature to obtain hot boric acid aqueous solution; under stirring at 60℃, the hot boric acid aqueous solution is slowly added dropwise to the aluminum isopropoxide-tetraethyl isopropoxide mixed alcohol solution, and the pH of the system is adjusted to 4.8 during the addition process. After the addition is completed, it is kept at the temperature for 4 hours for hydrolysis to obtain aluminum-boron-silicon composite sol; 50 parts of rare earth doped silica are added to the composite sol and ultrasonically dispersed for 2 hours; after drying at 110℃ for 4 hours, it is transferred to a tube furnace, heated to 800℃ and kept at the temperature for 2 hours, and then cooled with the furnace to obtain composite modified silica.
[0040] S2. Mix 90 parts of quartz sand, 20 parts of composite modified silica, 10 parts of borax, 10 parts of boric acid, 6 parts of alumina composite material, 2 parts of calcium oxide, 2 parts of sodium chloride, and 0.6 parts of chromium trioxide to obtain a mixture. Transfer the mixture to a glass melting furnace, first heat it to 900°C and hold it for 100 min, then heat it to 1300°C and hold it for 30 min, and then heat it to 1650°C and hold it for 120 min to obtain molten glass. S3. The glass melt described in step S2 is clarified and homogenized (temperature 1550℃, time 20min), pressed into shape (temperature 1050℃, pressure 15MPa), and annealed. First, it is cooled to 550℃ at a rate of 4℃ / min, and then cooled to room temperature at a rate of 8℃ / min to obtain wear-resistant, high-strength lake green borosilicate glass.
[0041] Preparation of alumina composite materials: 450 parts by weight of anhydrous ethanol and 50 parts by weight of deionized water were mixed, and 50 parts by weight of tetraethyl orthosilicate were added. The pH was adjusted to 5, and the mixture was stirred at room temperature for 20 minutes to obtain a precursor solution. Under a nitrogen inert atmosphere, 30 parts by weight of nano-alumina were dispersed in 100 parts by weight of anhydrous ethanol to obtain an alumina dispersion; 4 parts by weight of nano-carbon powder were dispersed in 20 parts by weight of anhydrous ethanol to obtain a carbon powder dispersion; and 1.2 parts by weight of nano-silicon powder were dispersed in 10 parts by weight of anhydrous ethanol to obtain a silicon powder dispersion. Alumina dispersion, carbon powder dispersion, and silicon powder dispersion were mixed and ultrasonically dispersed to obtain a powder-mixed ethanol dispersion. The precursor solution was then added, and the mixture was heated to 70°C and stirred for 4 hours to coat the alumina. After vacuum drying, an alumina-coated body was obtained. The alumina-coated body was placed in a high-pressure sintering apparatus, first subjected to a pressure of 5 GPa, then heated to 1600°C under a nitrogen atmosphere and held for 155 minutes. After cooling to room temperature, it was pulverized to obtain an alumina composite material. The XRD patterns of the alumina composite material and nano-alumina are shown below. Figure 1 As shown, the microstructure of the alumina composite material was analyzed, and its transmission electron microscopy (TEM) image is shown below. Figure 2 As shown. Example 2
[0042] This embodiment provides a method for preparing wear-resistant, high-strength, lake-green borosilicate glass, including the following steps: S1. By weight, 20 parts of lanthanum nitrate and 30 parts of yttrium nitrate were added to 180 parts of deionized water and stirred to dissolve, thus obtaining a rare earth precursor solution. Then, 40 parts of nano-silica were added for ultrasonic impregnation (ultrasonic power of 200W, ultrasonic frequency of 20kHz, impregnation temperature of 50℃, and impregnation time of 6h). After filtration, rare earth-impregnated silica was obtained. The rare earth-impregnated silica was transferred to a tube furnace, heated to 400℃ and held for 80min, then heated to 1200℃ and calcined for 6h. After cooling to room temperature, it was washed with deionized water and vacuum dried to obtain rare earth-doped silica. 20 parts of aluminum isopropoxide were dissolved in 30 parts of isopropanol, and then 10 parts of... Ethyl silicate was thoroughly stirred to obtain a mixed alcoholic solution of aluminum isopropoxide and ethyl silicate. Six parts of boric acid were added to 90 parts of deionized water, heated to 50°C, and stirred until the boric acid was completely dissolved. The solution was kept at this temperature to obtain a hot boric acid aqueous solution. Under stirring at 50°C, the hot boric acid aqueous solution was slowly added dropwise to the aluminum isopropoxide-ethyl silicate mixed alcoholic solution, with the pH of the system adjusted to 4.0 during the addition process. After the addition was complete, the solution was kept at this temperature for 2 hours to hydrolyze, yielding an aluminum-boron-silicon composite sol. Forty parts of rare earth-doped silica were added to the composite sol and ultrasonically dispersed for 1 hour. After drying at 100°C for 6 hours, the solution was transferred to a tube furnace, heated to 700°C, and kept at this temperature for 3 hours. The solution was then cooled in the furnace to obtain composite modified silica.
[0043] S2. Mix 80 parts of quartz sand, 10 parts of composite modified silica, 5 parts of borax, 5 parts of boric acid, 4 parts of alumina composite material, 1 part of calcium oxide, 1 part of potassium chloride, and 0.4 parts of chromium trioxide to obtain a mixture. Transfer the mixture to a glass melting furnace, first heat it to 850°C and hold it for 120 min, then heat it to 1250°C and hold it for 40 min, and then heat it to 1600°C and hold it for 140 min to obtain molten glass. S3. The glass melt described in step S2 is clarified and homogenized (temperature 1500℃, time 30min), pressed into shape (temperature 1000℃, pressure 20MPa), and annealed. First, it is cooled to 500℃ at a rate of 2℃ / min, and then cooled to room temperature at a rate of 6℃ / min to obtain wear-resistant, high-strength lake green borosilicate glass.
[0044] Preparation of alumina composite material: By weight, 400 parts of anhydrous ethanol and 100 parts of deionized water were mixed, 40 parts of tetraethyl orthosilicate were added, the pH was adjusted to 4, and the mixture was stirred at room temperature for 10 min to obtain a precursor solution; under a nitrogen inert protective atmosphere, 20 parts of nano-alumina were dispersed in 90 parts of anhydrous ethanol to obtain an alumina dispersion, 2 parts of nano-carbon powder were dispersed in 10 parts of anhydrous ethanol to obtain a carbon powder dispersion, and 0.8 parts of nano-silicon powder were dispersed in 8 parts of anhydrous ethanol to obtain a silicon powder dispersion. The alumina dispersion, carbon powder dispersion, and silicon powder dispersion were mixed and ultrasonically dispersed to obtain a powder-mixed ethanol dispersion. Then, the precursor solution was added, and the mixture was heated to 65°C and stirred for 6 h to coat the alumina. The mixture was then vacuum dried to obtain an alumina coated body; the alumina coated body was placed in a high-pressure sintering equipment, a pressure of 4 GPa was applied, and the temperature was raised to 1500°C and held for 25 min under a nitrogen atmosphere. The mixture was then cooled to room temperature and pulverized to obtain the alumina composite material. Example 3
[0045] This embodiment provides a method for preparing wear-resistant, high-strength, lake-green borosilicate glass, including the following steps: S1. By weight, 25 parts of lanthanum nitrate and 36 parts of yttrium nitrate were added to 190 parts of deionized water and stirred to dissolve, thus obtaining a rare earth precursor solution. Then, 48 parts of nano-silica were added for ultrasonic impregnation (ultrasonic power of 300W, ultrasonic frequency of 25kHz, impregnation temperature of 54℃, and impregnation time of 5h). After filtration, rare earth-impregnated silica was obtained. The rare earth-impregnated silica was transferred to a tube furnace, heated to 460℃ and held for 70min, then heated to 1250℃ and calcined for 5h. After cooling to room temperature, it was washed with deionized water and vacuum dried to obtain rare earth-doped silica. 24 parts of aluminum isopropoxide were dissolved in 40 parts of isopropanol, and then 16 parts of orthosilicic acid were added. Ethyl isopropoxide-tetraethyl isopropoxide mixed alcohol solution was obtained by thorough stirring. 7 parts of boric acid were added to 94 parts of deionized water, heated to 54℃ and stirred until the boric acid was completely dissolved. The solution was kept at this temperature to obtain a hot boric acid aqueous solution. Under stirring at 56℃, the hot boric acid aqueous solution was slowly added dropwise to the aluminum isopropoxide-tetraethyl isopropoxide mixed alcohol solution. The pH of the system was adjusted to 4.2 during the addition process. After the addition was completed, the solution was kept at this temperature for 3 hours to hydrolyze and obtain an aluminum-boron-silicon composite sol. 45 parts of rare earth-doped silica were added to the composite sol and ultrasonically dispersed for 1.5 hours. After drying at 105℃ for 5 hours, the solution was transferred to a tube furnace, heated to 760℃ and kept at this temperature for 2.4 hours. The solution was then cooled with the furnace to obtain composite modified silica.
[0046] S2. Mix 84 parts of quartz sand, 15 parts of composite modified silica, 8 parts of borax, 7 parts of boric acid, 5 parts of alumina composite material, 1.4 parts of calcium oxide, 1.6 parts of calcium sulfate, and 0.5 parts of chromium trioxide to obtain a mixture. Transfer the mixture to a glass melting furnace, first heat it to 880°C and hold it for 110 min, then heat it to 1280°C and hold it for 35 min, and then heat it to 1620°C and hold it for 130 min to obtain molten glass. S3. The glass melt described in step S2 is clarified and homogenized (temperature 1520℃, time 25min), pressed into shape (temperature 1020℃, pressure 18MPa), and annealed. First, it is cooled to 520℃ at a rate of 3℃ / min, and then cooled to room temperature at a rate of 7℃ / min to obtain wear-resistant, high-strength lake green borosilicate glass.
[0047] Preparation of alumina composite material: By weight, 420 parts of anhydrous ethanol and 80 parts of deionized water were mixed, 45 parts of tetraethyl orthosilicate were added, the pH was adjusted to 4.5, and the mixture was stirred at room temperature for 15 min to obtain a precursor solution; under a nitrogen inert protective atmosphere, 24 parts of nano-alumina were dispersed in 95 parts of anhydrous ethanol to obtain an alumina dispersion, 3 parts of nano-carbon powder were dispersed in 15 parts of anhydrous ethanol to obtain a carbon powder dispersion, and 0.9 parts of nano-silicon powder were dispersed in 9 parts of anhydrous ethanol to obtain a silicon powder dispersion. The alumina dispersion, carbon powder dispersion, and silicon powder dispersion were mixed and ultrasonically dispersed to obtain a powder-mixed ethanol dispersion. Then, the precursor solution was added, and the mixture was heated to 68°C and stirred for 5 h to coat the alumina. The mixture was then vacuum dried to obtain an alumina coated body; the alumina coated body was placed in a high-pressure sintering equipment, a pressure of 4.5 GPa was applied, and the temperature was raised to 1550°C and held for 19 min under a nitrogen atmosphere. The mixture was then cooled to room temperature and pulverized to obtain the alumina composite material.
[0048] Comparative Example 1 The difference between this comparative example and Example 1 is that nano-silica (item number S104596) is used instead of composite modified silica.
[0049] Comparative Example 2 The difference between this comparative example and Example 1 is that rare earth-doped silicon dioxide is used instead of composite modified silicon dioxide.
[0050] Comparative Example 3 The difference between this comparative example and Example 1 is that nano-alumina (item number A396574) is used instead of alumina composite material.
[0051] Performance testing: (1) Wear resistance: The steel wool abrasion tester was used to rub the sample surface back and forth 100 times with a test load of 500g. The transmittance before and after the abrasion was tested by a UV-Vis spectrometer at a wavelength of 400nm. The wear resistance was evaluated by calculating the decrease in transmittance. The less the transmittance decreased, the better the wear resistance.
[0052] (2) Bending strength: The test shall be conducted in accordance with the requirements of GB / T 37781-2019 Test method for bending strength of glass materials.
[0053] (3) Impact resistance: The test shall be conducted in accordance with the requirements of GB / T 39814-2021 Test method for impact resistance of ultra-thin glass by falling ball impact method.
[0054] The performance test data above are shown in Table 1.
[0055] Table 1 Performance Test Results
[0056] As can be seen from the above, the present invention first uses rare earth to dope nano-silica to obtain rare earth-doped silica, then modifies the rare earth-doped silica to obtain composite modified silica, and then mixes quartz sand, composite modified silica, borax, boric acid, alumina, calcium oxide, inorganic salt additives, and chromium trioxide to obtain a mixture, and melts the mixture at high temperature to obtain glass melt, which is then clarified, homogenized, pressed, and annealed to obtain wear-resistant, high-strength lake green high borosilicate glass (Examples 1 to 3), which has better comprehensive performance.
[0057] Compared with Example 1, the use of nano-silica (item number S104596) to replace composite modified silica resulted in a decrease in wear resistance and flexural strength due to the lack of the effect of composite modified silica (Comparative Example 1); compared with Example 1, the use of rare earth-doped silica to replace composite modified silica resulted in a decrease in wear resistance and flexural strength due to the lack of the effect of boroaluminosilicate coating layer (Comparative Example 2); compared with Example 1, the use of nano-alumina (item number A396574) to replace alumina composite material resulted in a decrease in wear resistance and flexural strength due to the lack of the effect of alumina composite material (Comparative Example 3).
Claims
1. A method for preparing wear-resistant, high-strength, lake-green borosilicate glass, characterized in that, Includes the following steps: S1. First, rare earth elements are used to dope nano-silica to obtain rare earth-doped silica, and then the rare earth-doped silica is modified to obtain composite modified silica. S2. Quartz sand, composite modified silica, borax, boric acid, alumina, calcium oxide, inorganic salt additives, and chromium trioxide are mixed to obtain a mixture. The mixture is then melted at high temperature to obtain molten glass. S3. The glass melt described in step S2 is clarified, homogenized, pressed, and annealed to obtain wear-resistant, high-strength lake green borosilicate glass.
2. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 1, characterized in that, The components in step S2, by weight, include: 80-90 parts of quartz sand, 10-20 parts of composite modified silica, 5-10 parts of borax, 5-10 parts of boric acid, 4-6 parts of alumina, 1-2 parts of calcium oxide, 1-2 parts of inorganic salt additives, and 0.4-0.6 parts of chromium trioxide.
3. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 1, characterized in that, The preparation steps of the rare earth-doped silica are as follows: by weight, 20-30 parts of lanthanum nitrate and 30-40 parts of yttrium nitrate are added to 180-200 parts of deionized water and stirred to dissolve to obtain a rare earth precursor solution. Then, 40-50 parts of nano silica are added for ultrasonic impregnation, filtered, and rare earth-impregnated silica is obtained. The rare earth-impregnated silica is then calcined at high temperature to obtain rare earth-doped silica.
4. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 3, characterized in that, The high-temperature calcination step is as follows: the rare earth impregnated silica is transferred to a tube furnace, heated to 400~500℃ and held for 60~80 minutes, then heated to 1200~1300℃ and calcined for 4~6 hours, cooled to room temperature, washed with deionized water, and vacuum dried.
5. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 1, characterized in that, The modification process is as follows: by weight, 20-30 parts of aluminum isopropoxide are dissolved in 30-50 parts of isopropanol, and then 10-20 parts of tetraethyl orthosilicate are added and stirred thoroughly to obtain an aluminum isopropoxide-tetraethyl orthosilicate mixed alcohol solution; 6-8 parts of boric acid are added to 90-100 parts of deionized water, heated to 50-60℃ and stirred until the boric acid is completely dissolved, and kept warm to obtain a hot boric acid aqueous solution; under stirring conditions at 50-60℃, the hot boric acid aqueous solution is added dropwise to the aluminum isopropoxide-tetraethyl orthosilicate mixed alcohol solution, and the pH of the system is adjusted to 4.0-4.8 during the dropwise addition process. After the dropwise addition is completed, the system is kept warm and hydrolyzed for 2-4 hours to obtain an aluminum-boron-silicon composite sol. Add 40-50 parts of rare earth-doped silica to the composite sol and ultrasonically disperse for 1-2 hours; dry at 100-110℃ for 4-6 hours and then transfer to a tube furnace, heat to 700-800℃ and hold for 2-3 hours, and cool with the furnace to obtain composite modified silica.
6. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 1, characterized in that, The alumina is an alumina composite material; the preparation method of the alumina composite material is as follows: first, nano-alumina, nano-carbon powder, and nano-silicon powder are added to a tetraethyl orthosilicate solution to prepare an alumina coating, and then the alumina coating is subjected to high temperature and high pressure treatment to obtain the alumina composite material.
7. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 6, characterized in that, The preparation steps of the alumina coating are as follows: by weight, 400-450 parts of anhydrous ethanol and 50-100 parts of deionized water are mixed, 40-50 parts of tetraethyl orthosilicate are added, the pH is adjusted to 4-5 and stirred at room temperature for 10-20 min to obtain a precursor solution; under a nitrogen inert protective atmosphere, 20-30 parts of nano-alumina are dispersed in 90-100 parts of anhydrous ethanol to obtain an alumina dispersion, 2-4 parts of nano-carbon powder are dispersed in 10-20 parts of anhydrous ethanol to obtain a carbon powder dispersion, and 0.8-1.2 parts of nano-silicon powder are dispersed in 8-10 parts of anhydrous ethanol to obtain a silicon powder dispersion. The alumina dispersion, carbon powder dispersion, and silicon powder dispersion are mixed and ultrasonically dispersed to obtain a powder-mixed ethanol dispersion. Then, the precursor solution is added and the mixture is heated to 65-70℃ and stirred for 4-6 h to coat the alumina, followed by vacuum drying to obtain the alumina coating.
8. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 6, characterized in that, The high-temperature and high-pressure treatment steps are as follows: the alumina coating is placed in a high-pressure sintering equipment, a pressure of 4~5 GPa is applied first, then the temperature is raised to 1500~1600℃ under a nitrogen atmosphere and held for 15~25 min, cooled to room temperature, and pulverized to obtain the alumina composite material.
9. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 1, characterized in that, The inorganic salt additive is selected from one or more of sodium chloride, potassium chloride, calcium sulfate, and zinc sulfate.
10. The method for preparing a wear-resistant, high-strength, lake-green borosilicate glass according to claim 1, characterized in that, The high-temperature melting step in step S2 is as follows: the mixture is transferred to a glass furnace, heated to 850~900℃ and held for 100~120 min, then heated to 1250~1300℃ and held for 30~40 min, and then heated to 1600~1650℃ and held for 120~140 min.
Citation Information
Patent Citations
A method for preparing highly transparent high borosilicate glass
CN119330589B